The META-Oak Project: Using Photovoice to Investigate Youth Perspectives on Tobacco Companies' Marketing of E-Cigarettes Toward Adolescents in Oakland. (July 2019) - Chopel, Alison; Lee, R. Eugene; Ortiz-Matute, Elizabeth; Peoples, Namiyé; Homer Vagadori, Kim; Curtis, Andrew; Ling, Pamela M.
The California Adolescent Health Collaborative, a project of the Public Health Institute, in partnership with the University of California, San Francisco's Center for Tobacco Control Research and Education jointly led a community-based participatory research (CBPR) study engaging youth coresearchers to fill the critical gap in knowledge about youth's perceptions of electronic cigarette products and how they are marketed toward young people in Oakland. Youth coresearchers who were trained as journalists partnered with the adult investigators to explore the e-cigarette topic from their perspective, embedded in the context of their own experiences and those of others in their communities. The goal of this exploratory CBPR study was to improve understanding of how and why youth (ages: 14-24 years) in Oakland are adopting (or resisting) e-cigarettes, how youth respond to increasing availability of e-cigarettes in their communities, and how they perceive communications about e-cigarettes (e.g., advertising) and in turn communicate about the products to each other.